Working efficiency of extension field staff with regards to integrated pest management of cotton in district D. G. Khan, Punjab, Pakistan - Muhammad Adeel1, Badar Naseem Siddiqui1, Waqar-Ul-Hassan Tareen , Adnan Rayit1 and Shah Fahd (JSSH, 2023)
In the agriculture sector, the success of any program and project depends upon the working efficiency of extension field staff (EFS). EFS are key stake holders and play crucial roles in the extension services, particularly in agriculture and rural development. Therefore, the present study was conducted to evaluate the working efficiency of extension field staff with special reference to IPM of cotton growers in district D. G. Khan. The results reveal that most of the respondents (44.2%) were under 35 years of age and about 80.80% of them were educated.